Statement of Surveillance Priorities-Revisions of Economic Priorities and Progress on Operational Priorities. (Policy Papers; Policy Paper ;, 2009)
This paper recommends changes to the economic priorities of the Statement of Surveillance Priorities (SSP) and provides an update on actions taken towards implementing the operational priorities.